Attributing technological bias to public goods - Alderman, Harold (Elsevier, 1984)
This note reports a modification of one use of the translog production function reported by Binswanger (1973, 1978). The method employed in this study recognizes that changes in factor shares over time are affected by a variety of decision variables including research and extension. In addition, some of the changes attributed to technical change may in fact be due to a change in the resource environment the individual decision maker faces, including the stock of public goods infrastructure. The study also investigates shifts in technological change which may be attributed to changes in the political climate.